An experimental note on the deformation and breakup of viscoelastic droplets rising in non-Newtonian fluids - Ortiz Martínez, Susana Lucía (Rheologica Acta, 2016)
The deformation of viscoelastic droplets rising in non-Newtonian fluids.
The deformation of viscoelastic droplets rising in non-Newtonian fluids.
Keywords: non-Newtonian fluids; deformation of fluids; flow around fluids; droplets rising in viscoelastic fluids; negative wake; fluidos no Newtonianos; cauda negativa; Fluidos Neewtonianos; Deformación de fluidos